Functional state of the body of elementary schoolchildren when using e-learning tools - I.E. Alexandrova; M.V. Ayzatova (LCC «Medicine-Inform», 2022)
I.E. Alexandrova1, M.V. Ayzatova1,2 1National Medical Research Center for Children's Health, Moscow, Russian Federation 2Moscow Center of Hygiene and Epidemiology, Moscow, Russian Federation Aim: to provide a physiological hygienic basis and regulation for using interactive panels (IP) in class to ensure safe learning in the digital environment. Patients and Methods: the following goals were set: (1) to compare the effects of interactive panels versus school board on the functional state of the body (FSB) of schoolchildren; (2) to analyze FSB of schoolchildren after classes with various duration of IP use. FSB of schoolchildren (mental and visual performance) in classes with the use of IPs (experimental class, n=28) or a classic chalk board (control class, n=26) were compared. A complex of hygienic, physiological, and statistical methods was applied. Results: based on a comparative analysis of mental capacity (MC) indicators of two classes, the tendency of lessons with the use of IPs showed the obvious and excessive fatigue more commonly registered among first-grade pupils (p<0.05), and the number of characters viewed in tests was decreased. The integral performance indicator of the class team changed more significantly after lessons with the use of IPs, reflecting the prevalence of "unsatisfactory" and "poor" proportions of performed proofreading tests over the number of "excellent" and "good". The specified indicator in the experimental class, being twice as high at the beginning of the school day, became 2 times lower by the end of classes versus the control class. The decrease in the parameters of the critical flicker fusion frequency (CFFF), indicating a deterioration in the functional state of the visual system, was more noticeable in the experimental class (p<0.01). The analysis of the average w eekly MC indicators also revealed that the control class made fewer mistakes in the tests, they had significantly fewer signs of obvious and excessive fatigue. Conclusion: schoolchildren with unregulated use of IPs (versus the control class equipped with the classic chalk board) commonly had adverse indicators of mental and visual performance. The permissible time for the use of IPs during the lesson was justified, the excess of which leads to a significantly more negative trend among children's FSB indicators. Keywords: prevention, schoolchildren, hygienic regulations, excessive fatigue, interactive panels. For citation: Alexandrova I.E., Ayzatova M.V. Functional state of the body of elementary schoolchildren when using e-learning tools. Russian Journal of Woman and Child Health. 2022;5(2):157-163 (in Russ.). DOI: 10.32364/2618-8430-2022-5-2-157-163.